Accounting Functions Outsourcing and SMEs: Empirical Evidence from Iran - Kamyabi, Yahya; Susela Devi S (Faculty of Business Management, UiTM Terengganu, 2011)
The purpose of this paper is to examine the factors that influence the outsourcing of accounting functions in Iranian manufacturing small and medium enterprises (SMEs). Using transaction cost economics (TCE) and resource-based theories, results from a questionnaire survey of 658 SMEs show that outsourcing of accounting functions is positively associated with trust of the SME owner/manager in an external accountant. In addition, the technical competence is positively and significantly related to outsourcing, but firm size was not supported in our sample.